Data Mining dalam Menganalisis Faktor Alasan Pemilihan Perumahan - Erlin Elisa; Alfannisa Annurullah Fajrin (Prosiding, 2020)
The house is a basic human need, where the house is a means of resting and gathering with the family, the choice of housing type greatly affects the comfort of someone who will live in the house, such as choosing where the location, facilities, accessibility and even more important is the price that fits the pocket of the candidate. housing owners, this study discusses analysis in the selection of housing in batam city, the variables used are the accessibility factors related to distance and ease of reaching a place., typology is related to the size of the settlement, price, payment for houses, data analysis is carried out with the concept of extracting information on the C4.5 algorithm by testing the results and obtaining the decision tree using the opensource rapidminer tools. From the data processing, the result shows that the factors that really influence people to choose and buy a house in the research object are price, accessibility and typology.